EVALUATION OF MULTIDISCIPLINARY EDUCATION ON DIET MODIFICATION AND FLUID INTAKE RESTRICTION ADHERENCE AMONG THE CHRONIC KIDNEY DISEASE PATIENTS IN HEMODIALYSIS UNIT OF GENERAL HOSPITAL IN KUANTAN - Siti Noorkhairina S.; A. G., Nor Amalina (International Journal of Allied Health Sciences, 2019)
Patients with chronic kidney disease may have a deteriorated condition that may lead to end-stage renal disease. Growing incidence and prevalence of CKD in Malaysia required an evaluation of knowledge and adherence level throughout disease management. Thus, this study was conducted to determine the sociodemographic background, level of satisfaction on the education received, level of diet modification and fluid intake restriction adherence among the CKD patients. A survey was purposely conducted among 58 CKD patients attended the Hemodialysis Unit, Hospital Tengku Ampuan Afzan, Kuantan, Pahang. A validated questionnaire was used to collect the data. Results were analysed descriptively and Fisher’s Exact Test for univariate. Level of significance was set at p-value less than 0.05. Half of the patients were aged 50 years or more, male (58.6%), Malays (82.8%), married (67.2%), having normal BMI (75.9%), completed secondary school (65.5%) and unemployed (43.1%). There was no association between sociodemographic background and diet modification adherence except for BMI (p=0.052). Similarly, no association between sociodemographic background and fluid intake restriction adherence except for marital status (p=0.034). Finally, there was no association between the level of satisfaction on education received about CKD in regards to diet modification and fluid intake restriction adherence. This study reported moderate adherence for diet modification and fluid intake restriction, respectively. Overall, they have equally rated moderate (50.0%) and high (50.0%) satisfaction in education received about CKD during treatment. Multidisciplinary approach in managing CKD disease through educational intervention had proven to improve patients’ satisfaction.